Role of Advertisement in Achieving Frowth in Sales and Services of A Business - Saju K James, Dr Abhiram Kulshreshtha, (International Journal of Scientific Research and Management (IJSRM), 2015)
Advertisement plays an important role in achieving growth in sales of product and services. Effective advertising refers to informing the public about the right product at the right time through the right medium. The right media selection is the crux of the success of the entire advertising campaign. With more than two billion users around the world, the potential reach alone has advertisers drooling. Advertisement, in the present atmosphere of global competition, is a powerful social and economic force. Consumers look to it for information in respect of products, brands and services that might help them in selection and to meet their material needs. Without these services immediate contact is not possible while sitting away from home and at a distant place.